APPLICATION OF METAL COMPLEXES OF SCHIFF BASES AS AN ANTIMICROBIAL DRUG: A REVIEW OF RECENT WORKS - Divya, Kumble; Pinto, Geetha M.; Pinto, Asha F (International Journal of Current Pharmaceutical Research, 2017)
Schiff bases are versatile ligands which are synthesized from the condensation of primary amines with carbonyl groups. Synthesis of Schiff base transition metal complexes by using Schiff base as ligands appears to be fascinating in view of the possibility of obtaining coordination compounds of unusual structure and stability. These transition metal complexes have received exceptional consideration because of their active part in metalloenzymes and as biomimetic model compounds due to their closeness to natural proteins and enzymes. These compounds are very important in pharmaceutical fields because of their wide spectrum of biological activities. Most of them show biological activities including antibacterial, antifungal, antidiabetic, antitumor, antiproliferative, anticancer, herbicidal, and anti-inflammatory activities. The biological activity of the transition metal complexes derived from the Schiff base ligands has been widely studied. This review summarizes the importance, Scope and antimicrobial activities of Schiff base metal complexes.